Childs life satisfaction as a mediator of perceived maternal parenting style in having obsessive-compulsive personality disorder (OCPD) symptoms - Ongson, Beverly Denice T. (Animo Repository, 2018)
The purpose of this study is to explain the potential psychological mechanism of how childhood satisfaction can influence the relationship of an individuals perceived authoritarian maternal parenting style on predicting Obsessive Compulsive Personality Disorder (OCPD) symptom development during early adulthood. Results showed that high authoritarian scores predicted low childhood satisfaction and high OCPD symptoms, respectively. But childhood satisfaction failed to predict OCPD, indicating that relying only to how satisfied an individual was during his childhood, makes it unsubstantial to assume that he or she will develop OCPD symptoms. This is inconsistent with previous literatures which indicated the significant relationship of child life satisfaction and OCPD symptoms. Absence of mediation was also established. The findings in this study provided an implication for the importance of clinical and maternal intervention in producing psychologically healthy individuals.